Pengaruh Kompetensi Kepala Sekolah terhadap Kinerja Guru (Studi Deskrifsi Analitik pada SD Negeri di Wilayah Kabupaten Pangandaran) - Sobirin Sobirin (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
The ideal view of the professionalism of school principals is reflected in the image of future principals, namely principals who have expertise, responsibility, and a sense of fellowship supported by strong professional ethics. Some school supervisor notesin Cijulang sub-district are more principals whose competence is still below the standard. Therefore, this research takes the title: "The Influence of Principal Competence on Teacher Performance". where this research is a study of several Regional Public Elementary Schools in Pangandaran Regency". This study aims to examine the influence of the principal's competence on teacher performance at public elementary schools in the Pangandaran Regency. The method used in this research is descriptive analytical method with a quantitative approach. The population of the study was all public elementary schools located in the Pangandaran Regency, which amounted to 293 schools. Sampling using random sampling technique that is determining the sample randomly by determining 50% of the total population. The research data is in accordance with the operational variables, taken using a research questionnaire technique. The conclusion of the study is that together there is a positive and significant influence of managerial competence, supervisory competence, entrepreneurial competence, personality competence, and principal's social competence on teacher performance.